Discoaster zonation of the Miocene of the Kutei Basin, East Kalimantan, Indonesia (Mahakam Delta Offshore) - Lambert Bernard; Laporte-Galaa Cécile (Carnets de Géologie, 2005)
Thirteen time-stratigraphic associations of the nannofossil Discoaster have been defined and used in the Miocene Kutei Basin of eastern Borneo to establish a regional stratigraphic framework. The methodology used is discussed and the fossils employed are figured and annotated. Their aid in resolving the timing, stages and details of delta construction is presented graphically.